THE INFLUENCE OF LIFESTYLE AND POPULARITY ON BUYING DECISION AND BRAND EXPERIENCE VARIO MOTORCYCLE (CASE STUDY OF THE VILLAGE TEMBILAHAN KOTA KECAMATAN TEMBILAHAN DISTRICT INDRAGIRI DOWN) - Firmansyah, Firmansyah (International Journal of Business and Information Technology, 2020)
The development of the industrial world, especially the automotive industry in Indonesia, has experienced quite a significant development, this is indicated by the number of requests which each year increases, in line with the needs and demands of the community for adequate transportation facilities. Indonesian people, especially in the city of Tembilahan, are now more fond of automatic motorbikes than the duck type. The type of duck motorbike is a type of small motorcycle that is built on a frame which mostly consists of a large diameter pipe. There are several factors that researchers see that occur in the field, especially in purchasing products, namely the lifestyle in the environment and the existing popularity. The results of the study: Lifestyle has no effect on purchasing decisions with. Popularity influences purchasing decisions Lifestyle and popularity influence purchasing decisions as a whole. And the path analysis obtained an indirect effect of lifestyle on brand experience through purchasing decisions, namely -, 125%, while the indirect effect of popularity on brand experience through purchasing decisions is 7.14%.